2009
DOI: 10.1016/j.psychres.2008.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Perceived criticism: Associations with perceiver characteristics and interpersonal behaviour

Abstract: a b s t r a c t a r t i c l e i n f oPerceived Criticism (PC) evolved in the context of Expressed Emotion (EE) research and, like EE, predicts the course of various psychiatric disorders. However, little is known about PC's validity. We examined (in Study 1) to what extent PC reflects the perceiver's current depressive and marital complaints, whether PC measures reciprocal criticism that characterizes dyads rather than individuals, and (in Study 2) whether PC reflects actual interactive behaviour. Both studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However, in a study on students [22], the data suggested that it was unlikely that perceived criticism simply reflected the negatively biased perceptions of distressed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a study on students [22], the data suggested that it was unlikely that perceived criticism simply reflected the negatively biased perceptions of distressed individuals.…”
Section: Discussionmentioning
confidence: 99%